Exposing the dark side: phubbing as a detrimental consequence in the digital era - Erwinda, Lira (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
In the digital era, the phenomenon of phubbing has emerged as a detrimental consequence associated with the use of technology. Phubbing refers to behavior in which a person is too focused on their electronic device, such as a smartphone, while interacting with other people. This study aims to reveal the dark side of phubbing and its negative impact on social relations in an increasingly digitally connected era. This study uses literature analysis and related research, it is found that phubbing can threaten the quality of interpersonal relationships. When someone engages in phubbing, they ignore the physical presence of those around them, leaving others feeling neglected, unappreciated, and lonely. In addition, phubbing also interferes with healthy human communication, leading to shallow communication disorders, lack of empathy, and difficulties in building meaningful relationships. In facing these adverse consequences, research also underscores the importance of implementing strategies and policies that educate the public about the wise use of information technology. In addition, personal approaches such as increasing self-awareness about phubbing behavior and adopting habits that balance the use of technology and social interaction can also help reduce the negative effects of phubbing.